Dukungan dan Peran Kelembagaan dalam Meningkatkan Kemandirian Petani Kakao di Provinsi Sulawesi Tengah - Andri Amaliel Managanta; Sumardjo Sumardjo; Dwi Sadono; Prabowo Tjitropranoto (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Indonesia is the third largest cocoa producer in the world after Ivory Coast and Ghana. Central Sulawesi is a center of Indonesian cocoa commodity, yet has low improvement. This is presumably due to the lack of support of farmer institutions that were formed not based on farmers' needs or the interests of farmers. The objectives of this study were to: (1) analyze the level of institutional support for cocoa farmers in Central Sulawesi Province, and (2) analyze the role and strategy of increasing institutional support for cocoa farmers in Central Sulawesi Province. The study was conducted in four districts in Central Sulawesi Province: Poso, Sigi, Morowali Utara and Donggala Regencies. The research sample was 380 farmers. To describe the research variables used descriptive statistical analysis in the frequency table and Duncan’s Multiple Range Test (DMRT). The results showed that most farmers (70.2%–98.7%) assessed that institutional support in the contexts of marketing, capital, processing, and technical guidance were relatively low so it tended to be less conducive to increasing farmers' independence. The institutional role of those four contexts was also low categoryzed (26.6–43.0) so that it needs serious attention in an effort to increase the weak independence of farmers.